DAMPAK PENERAPAN GOOD UNIVERSITY GOVERNANCE TERHADAP KINERJA MANAJERIAL MELALUI IMPLEMENTASI ANGGARAN BERBASIS PARTISIPATIF - Amilin, Amilin (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2016)
The purpose of this study to examine the impact of the implementation of Good University Governance Principles on managerial performance in the practice of participatory-based budget management. The units in UIN Syarif Hidayatullah Jakarta as the population of the study.Samples were selected from the units that perform a budget management. The number of respondents, 60 people who have a structural position in around UIN Syarif Hidayatullah Jakarta who served as: Vice-Chancellor, Vice Dean, Head of Departement, Bureau Chief, Head of Division, Chief of Section, Directorate of Internal Control System. Testing data using a Path Analysis Method. The results of the study are: First, the application of Good University Governance Principles at UIN Syarif Hidayatullah Jakarta influence onmanagerial performance; and Second, the practice of participatory-based budget managementat UIN Syarif Hidayatullah Jakarta have not been able to encourage the application of Good University Governance Principles in influencing managerial performance. The results of the study is important for university officials as a reference in a practice of participatory-based budget managementby applying Good University Governance principles to achieve the best performance.